Thermal management in high-power lithium-ion Batteries: Synergistic effects of phase change material thickness, graphene enhancers, and active cooling systems - Saeed Rahmanian; Hossein Rahmanian-Koushkaki; Khashayar Hosseinzadeh (Case Studies in Thermal Engineering)
Effective thermal management is critical to mitigating thermal runaway risks, optimizing performance, and extending the operational lifespan of lithium-ion batteries (LIBs) in high-rate applications. This study systematically evaluates four thermal management strategies for a 14.6 Ah LIB under aggressive discharge currents (1C, 3C, 5C): (1) baseline (no thermal control), (2) phase change material (PCM) with thickness variations, (3) hybrid PCM-K-enhancer (copper foam, graphene, metal plates) systems, and (4) active cooling (heat pipes + forced air convection). High-fidelity 3D simulations in ANSYS Fluent V22 quantified temperature uniformity, peak temperature suppression, and transient phase change behavior.At 5C discharge, baseline tests revealed unsafe peak temperatures of 84.03 °C. PCM thickness optimization demonstrated a nonlinear cooling effect: 1 mm PCM reduced peak temperature to 66.91 °C, while 3 mm PCM achieved 55.38 °C, underscoring the role of latent heat capacity scaling. Graphene-based K-enhancers outperformed copper foam and metal plates, synergizing with PCM to limit temperatures to 47.82 °C through thermal bridging. Synergistic integration of optimized PCM thickness (2 mm), graphene-enhanced thermal bridges, and heat-pipe cooling achieved a 53.3 % temperature reduction vs. baseline (39.23 °C).The study introduces a hierarchical thermal management framework, demonstrating that hybrid systems integrating optimized PCM thickness, graphene-enhanced interfacial conductivity, and active cooling achieve superior thermal equilibrium. These findings advance the design of multi-scale thermal regulation strategies for high-power LIB packs in electric vehicles.